Proceedings of the Seventh International Conference on Animal-Computer Interaction 2020
DOI: 10.1145/3446002.3446003
|View full text |Cite
|
Sign up to set email alerts
|

Designing Technologies for Playful Interspecies Communication

Abstract: This one-day workshop examines how we might use technologies to support design for playful interspecies communication and considers some of the potential implications. Here we explore aspects of playful technology and reflect on what opportunities computers can provide for facilitating communication between species. The workshop's focal activity will be the co-creation of some theoretical systems designed for specific multi-species scenarios. Through our activities, we aim to pave the way for designing technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…To explore interspecies communication further from an ethical perspective required an imaginative leap into an impersonal future, rather than a critique of established practice. Prior work has suggested that speculative design is useful both to ACI [61,45,32] and within the context of playful systems [23]. We therefore concluded that playful systems would be the most suitable vehicles for a speculative design challenge since play offers a universal open gateway for engagement and interaction.…”
Section: Context and Motivationmentioning
confidence: 83%
See 3 more Smart Citations
“…To explore interspecies communication further from an ethical perspective required an imaginative leap into an impersonal future, rather than a critique of established practice. Prior work has suggested that speculative design is useful both to ACI [61,45,32] and within the context of playful systems [23]. We therefore concluded that playful systems would be the most suitable vehicles for a speculative design challenge since play offers a universal open gateway for engagement and interaction.…”
Section: Context and Motivationmentioning
confidence: 83%
“…Play also occurs between humans and other domesticated species, such as cats [55]and horses [65], while playful experiences have been observed between various nonhuman species, including primates [74], dogs with horses [46] and dolphins with whales [16]. As noted in our earlier work [23]:…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Using such methods for primates in zoo contexts is incredibly complex because multiple stakeholders are involved [18], including zoo visitors, the animals, the keepers, the research directors and so on. Regarding design with animals in zoos, researchers have employed methods such as participatory design and co-design with elephants [10] and orangutans [59]. While primates worldwide are the key users of computer systems in zoos, much attention has been focused on great apes species [59] and little on monkeys.…”
Section: Introductionmentioning
confidence: 99%